2017
DOI: 10.18805/lr-366
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa olifera leaf extracts on growth and productivity of three leguminous crops

Abstract: Different concentrations of Moringa leaf extract were used to evaluate their effects on three leguminous crops (Alfalfa and Clitoria as forage crops and Mung bean as grain legume) Three independent experiments were carried out at King Abdulaziz University Experimental Station in Makkah province during 2015 and 2016. Treatments consisted of four concentrations of Moringa leaf extract (C1=1ml of juice+10 ml of distilled water, C2=1ml of juice+20ml of distilled water, C3=1ml of juice+30 ml of distilled water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…No variation in seed yield was observed due interaction effect. The previous experiment results noted by Chaudhari (2013) [6] in green gram and Rathva (2013) [14] in pigeon pea, Abohassan and Abusuwar (2018) [1] in green gram, Gunasekar et al (2018) [8] , Nivethadevi et al (2021) [13] in black gram and Irshad et al (2022) [9] in chickpea were found to be closely related with the findings of present research work.…”
Section: Resultssupporting
confidence: 88%
“…No variation in seed yield was observed due interaction effect. The previous experiment results noted by Chaudhari (2013) [6] in green gram and Rathva (2013) [14] in pigeon pea, Abohassan and Abusuwar (2018) [1] in green gram, Gunasekar et al (2018) [8] , Nivethadevi et al (2021) [13] in black gram and Irshad et al (2022) [9] in chickpea were found to be closely related with the findings of present research work.…”
Section: Resultssupporting
confidence: 88%
“…No variation in seed yield was observed due interaction effect. The previous experiment results noted by Chaudhari [20] in green gram and Rathva [21] in pigeon pea, Abohassan and Abusuwar [22] in green gram, Gunasekar et al [23]; Nivethadevi et al [24] in black gram and Irshad et al [25] in chickpea were found to be closely related with the findings of present research work.…”
Section: Seed Yieldsupporting
confidence: 89%
“…No variation in seed yield was observed due interaction effect. The previous experiment results noted by Chaudhari [9] in green gram and Rathva [10] in pigeon pea, Abohassan and Abusuwar [11] in green gram, Gunasekar et al [12], Nivethadevi et al [13] in black gram and Irshad et al [14] in chickpea were found to be closely related with the findings of present research work.…”
Section: Seed Yieldsupporting
confidence: 89%